Community pharmacists' opinions on skill-mix and delegation in England. (6th December 2017) - Barnes, Emma; Bullock, Alison; Allan, Margaret; Hodson, Karen
Abstract: Objectives: Following the 2005 contractual framework amendment, the expanding role of community pharmacy team members required a shift in entrenched views on roles and duties. This study aimed to report on community pharmacists' opinions on skill mix and explore how they can be addressed so that skill mix may be optimised. Methods: An invitation to complete an online questionnaire was distributed via email, marked for the attention of the lead pharmacist. Following a low response, a paper-based questionnaire was sent to all community pharmacies in England ( n = 11, 816). Questions elicited data about the respondent, the pharmacy (including staffing profile) and opinions on skill mix. Key findings: A total of 1154 returns were received, representing a 10% response rate. Of these, most were pharmacy chains (76%; n = 877), with 5–9 staff (54%; n = 600); commonly open 40–49 hours (42%; n = 487), dispensing <6000 prescriptions per week (41%, n = 533). From 26 statements on skill mix, three factors were identified by principal-components factor analysis: 'working well', 'feeling the pressure' and 'open to development'. Characteristics associated with 'working well': pharmacy owners, single businesses, with pharmacy technician(s), dispensing fewer prescriptions and open shorter hours. Characteristics associated with 'feeling the pressure': pharmacy chains, open longer hours, large numbers of prescriptions and relief pharmacists. Characteristics associated with 'open to development': recently qualified, second pharmacists, working longer hours, chains and dispensing lower numbers of prescriptions. Conclusions: Although limited by a low response, results suggest being in a position to influence (more experienced, business owners) may be associated with more positive opinions. Further training (including about legalities and leadership) could contribute to optimising skill mix in community pharmacies.